Limitations of Cyborg feminism in India and Misinterpretation of feminism in Western Cyborg science fiction movies in the light of Haraway’s The Cyborg Manifesto - Dalvin, Nesie (International Journal of Humanities and Education Development (IJHED), 2023)
In the light Donna Haraway’s work The Cyborg Manifesto this paper analyses the difficulties of adapting Cyborg model of feminism in a developing country like India. Initially the concept of cyborg feminism (Bell, 108) as introduced by Haraway is used to analyse the implicit ideology of Western cyborg science fiction movies. Through the analysis of popular western cyborg movies like Alita: Battle Angel (2019) and Blade Runner 2049 (2017), the absence of gender duality in cyborg world as predicted by Donna Haraway is proved wrong. Later the concept of cyborg feminism in the present society is shown to be inadequate showing the glass ceiling effect and how technology is sided with patriarchy. Finally the limitation of Cyborg feminism especially in a third world country like India is revealed considering its historical, political and cultural diversity. Socialist feminism and identity politics is more essential in the present society than a foreseeing women’s liberation in a technically developed future.